L3T4 and Lyt-2 T cells are both involved in the generation of low-dose streptozotocin-induced diabetes in mice. - Kantwerk, G; Cobbold, S; Waldmann, H; Kolb, H (1987)
In order to determine the role of different T lymphocyte subsets in the pathogenesis of low-dose streptozotocin (LD-Sz) induced diabetes, we treated mice with Sz together with repeated injections of rat monoclonal antibodies (MoAb) with specificity towards the mouse T cell differentiation markers L3T4 ('helper/inducer' T cells and some macrophages), Lyt-2 ('cytotoxic/suppressor' T cells and NK cells) and Thy-1 (pan T lymphocytes). Treatment depleted target cells in peripheral blood and spleen; decreased the ability of spleen cells to respond to mitogens; and, in the case of depletion of the L3T4 T cell subset, prevented a humoral immune response to SRBC. Treatment with MoAb against either of the two T cell subtypes could protect from hyperglycaemia and loss of body weight, suggesting that both T cell subsets were implicated in the development of LD-Sz induced diabetes. Immunocytochemical analysis of pancreatic sections showed that both L3T4+ and Lyt-2+ cells participated in islet infiltration together with macrophages. Treatment with MoAb markedly reduced islet infiltration by both L3T4+ and Lyt-2+ cells but not by macrophages. The suppressive effect of MoAb against either L3T4 or Lyt-2 on diabetes development suggests that the pathomechanism involved is different from that in experimental autoimmune neuritis and adjuvant arthritis where Lyt-2 cells are not involved.